Associations between activity and participation in adults with multiple sclerosis: a cross sectional study. Issue 4 (December 2019) - Ryan, Jennifer M.; Stennett, Andrea M.; Peacock, Sarah; Baker, Gayle; Norris, Meriel
Abstract: Objectives: The aim of this study was to determine the association between walking ability in a clinical setting (activity capacity), walking ability in a person's daily environment (activity capability) and walking performance in daily life (activity performance), and the contribution of each activity construct to participation among people with multiple sclerosis (MS). Design: Cross-sectional study. Setting: Five MS therapy centres in England. Participants: Fifty-two adults (13 males) with MS who were independently ambulatory with or without a walking aid (mean (SD) age 55.4 (9.1) year). Interventions: No intervention. Main outcome measures: Activity capacity, capability, and performance were assessed using the Six Minute Walk Test (6MWT), Twelve Item MS Walking Scale (MSWS-12), and steps/day measured using a pedometer worn for 6 days, respectively. Participation was assessed using the Impact on Participation and Autonomy questionnaire (IPA). Results: Distance walked on the 6MWT was associated with MSWS-12 score ( β  = −0.56, 95% CI −0.87 to −0.22) and steps/day ( β  = 129.49, 95% CI 48.48 to 207.57). MSWS-12 score was also associated with step count ( β  = −87.35, 95% CI −172.29 to −15.71). 6MWT distance was associated with the autonomy indoors subscale of the IPA ( β  = −0.02, 95% CI −0.04 to −0.01). No other activity measure was associated with participation. Conclusions: Findings suggest that while activity capacity, capability and performance are related, activity is a poor predictor of participation. The strength of associations between constructs of activity, and activity and participation, however, are often small with wide confidence intervals, indicating that there is considerable uncertainty associated with effect estimates.